Correlação entre medo odontológico, cárie dentária e hipomineralização molar-incisivo em escolares de 8 a 10 anos de idade - Laureano, Isla Camilla Carvalho (2019)
Studies involving the evaluation of dental fear became even more relevant as this became better understood by scientific community. Considering this, the present cross-sectional study aimed to correlate dental fear with dental caries and MIH in schoolchildren aged 8 to 10 years, in the city of Campina Grande / PB. The probabilistic sample, by clusters, was composed of 466 students of both sexes, from the urban municipal public elementary schools and the children were evaluated for dental fear, using the validated Brazilian version of the Children’s Fear Survey Schedule-Dental Subscale (CFSS-DS), and for the diagnosis of the dental caries experience, being the data obtained by three calibrated examiners, by the International Caries Detection & Assessment System (ICDAS II), obtaining inter Kappa from 0.80 to 0.90 and intra examiners from 0.71 to 0.75, and MIH, by a previously validated index, with inter Kappa from 0.61 to 0.72 and intraexaminer from 0.67 to 0.83. Descriptive analysis of the data and use of Chi-Square, U-Mann-Whitney and Spearman correlation were performed. The Poisson regression, with robust variance, was used for the multivariate analysis, with its respective confidence intervals (95% CI), and the variables with p <0.20 were included in the regression model; the level of significance was 5%. The prevalence of dental fear was 22.1%. In the bivariate analysis, dental fear was associated with monthly family income (p = 0.044) and dental caries (p = 0.021), while in the crude analysis dental fear was associated with monthly family income (PR = 0.651; (95% CI: 1.051-5.766), and in the adjusted, only associated with the monthly family income (PR = 0.656, 95% CI: 0.438-0.982). Significant differences were found between the sexes in the items "A person you do not know to touch you" (p = 0.020), "Someone looking at you" (p = 0.039) and "Someone putting instruments in your mouth" (p = 0.017) and "One person you do not know to touch you" (p = 0.039), and among children with MIH in the item "Anesthesia" (P = 0.003). Weak positive correlations were found between the total score of CFSS-DS and the number of caries teeth (r = 0.130, p <0.01) and between the total score of the CFSS-DS and the number of teeth with moderate / extensive stage caries (r = 0.135, p <0.01). Regarding the items of the CFSS-DS questionnaire and the number of teeth with severe MIH, fair negative correlations were observed (r = -0.263; p <0.05, r = -0.293; p <0.05) for “Someone to put instruments in your mouth” and “Having to go to the hospital” respectively. It was concluded that the prevalence of dental fear was high in children, and those with dental fear presented a correlation with dental caries and its most severe form, but did not demonstrate a correlation with the presence of Molar-Incisor Hypomineralisation nor with the degree more serious of this condition.